Highly sensitive dual‐mode relative humidity sensor based on integrated SAW and LC resonators. Issue 16 (1st August 2015) - Lu, D.; Zheng, Y.; Penirschke, A.; Jakoby, R.
Abstract : A dual‐mode relative humidity (RH) sensor is fabricated based on a surface acoustic wave (SAW) resonator with anti‐corrosive gold electrodes. The reflectors of the SAW resonator consist of two interdigital capacitors with loaded polyvinyl‐alcohol (PVA) films as sensitive layers, which further form a LC resonator operating below the SAW resonance frequency. With this sensor configuration, two sensing mechanisms are realised. The SAW resonator senses the mass loading of the PVA film with an average sensitivity of 0.38 × 10 −4 /%RH and a minimum electrical quality factor Q of 267 from 14.2% to its cutoff RH of 72.4%. The LC resonator senses the permittivity of the PVA film, which extends the operation range of the sensor to 89.3%RH with an average sensitivity of 4.79 × 10 −4 /%RH and a minimum Q factor of 8.7. Furthermore, a figure of merit (FoM) is defined and extracted from measurements to evaluate both the sensitivity and the Q factor. Below the cutoff RH, the sensor is preferable for use for the SAW resonator for RH sensing because of its better FoM. Above the cutoff RH, the SAW resonator is out of function, and the LC resonator is used instead with a good FoM.